A comparative study between audiological and speech outcomes of non-implantable wearing options for BAHA in the pediatric population - Garrada, Mohammad; Zimmo, Ziad Faisal; Alsulami, Meaad; Alkhatib, Talal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The aim of the study was to determine the audiological benefit of the current BAHAs sound processor worn on a SoundArc and to compare it to the known Softband in terms of soundField hearing thresholds and speech understanding in patients who have purely conductive, mixed, or SSD hearing loss. Methods: A cross-sectional study looking at children with conductive, mixed, or SSD hearing loss who are not candidates for middle ear surgery, canalplasty, or standard hearing aids. At the baseline visit, pure-tone audiograms were obtained, including masked/unmasked air- and bone conduction thresholds with speech recognition scores. Results: After two weeks of using programmed processors with Softband and SoundArc, all children were examined. The threshold for aided pure-tone audiometry was tested twice through each of the two transmission paths. The aided pure-tone audiometry threshold demonstrated a statistically significant improvement in PTA. The mean air-conduction thresholds for frequencies (0.5 to 4 kHz) were 63 dB, while the aided mean thresholds with the device (with Softband and SoundArc) was 35 dB. When compared to the unaided scenario, a statistically significant improvement of 98 percent (SoundArc) to 96 percent (Softband) was found at 65 dBSPL. There were no statistically significant differences between any of the ensembles (p=0.261). Conclusions: The results of our study suggest that subjects with conductive, mixed, or single-sided deafness hearing loss aided with BAHA sound processor worn on SoundArc or on a Softband can cause a significant improvement in terms of soundfield hearing threshold and speech understanding when compared to unaided conditions.